MODERN EPIDEMIOLOGICAL ASPECTS AND CRITERIA FOR DIAGNOSING PROSTATE CANCER - Arman Khozhayev; Yerzhan Nurdauletov; Bakbergen Zharkynovich; Serik Koishanov; Kurmangazy Demesinov; Kristina Sablukova; Maratbek Yerdenbek; Zhasulan Galymbek; Shero Valiev (Interdisciplinary Science Studies, 2024)
This scientific and analytical work presents modern global and local-regional epidemiological data and algorithms for complex diagnostics of such a common oncological pathology as prostate cancer. The issues of etiology and pathogenesis, features of distribution, as well as three basic principles of diagnosis are covered in detail: the role of prostate biomarkers, methods of visualization and histological verification. The epidemiological characteristics of this pathology in our republic are presented in the context of regions of the country.